Multi-objective optimal design and seismic performance of negative stiffness damped outrigger structures considering damping cost - Sun, Fei-Fei; Wang, Meng; Nagarajaiah, Satish (Engineering structures, 2021)
•Building direct connection between NSDO parameters and seismic responses.•Proposing an optimization method on harmful drift, acceleration and damping cost.•Retrofitting existing CO structure with supplemental NSDO in resisting earthquakes. In this paper, the seismic performance of conventional damped outrigger (CDO) is improved by incorporating negative stiffness (NS) in parallel with the viscous damper. The applied negative stiffness spring upgrades the classical Maxwell damping element, which is used to describe the assembly of outrigger viscous damper and perimeter columns, to negative stiffness amplifying damper with higher damping effect. Tall buildings with such negative stiffness damped outrigger (NSDO) is described in the state space expression of the structure-outrigger-excitation augmented assembly, and the root-mean-square (RMS) responses of NSDO structures are parametrically studied to develop a direct connection between outrigger parameters and structural seismic responses. Based on these results, a multi-objective optimization method with both performance and economic objectives—reducing harmful inter-story drift and structural acceleration simultaneously with less outrigger damping cost—is proposed. Finally, this optimally designed NSDO is used to retrofit existing conventional outrigger (CO) structures as a supplemental energy dissipation outrigger. The performance of this retrofitted structure is studied and compared with that retrofitted by optimal CDO under numerous real earthquake records. Result indicates the CO structure retrofitted by NSDO substantially saves the outrigger damping cost of CDO by 85.9%, and further decreases the harmful drift and structural acceleration responses over 51% and 29%, respectively. Although optimal design of NSDO for strong earthquakes alone is the focus of this study, it is shown that NSDO is able to reduce wind-induced maximum acceleration by 33% without amplifying wind-induced maximum harmful drift.